2015
DOI: 10.1055/s-0035-1565258
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Sensitivity of Intraoperative Motor Evoked Potential Monitoring in Predicting Postoperative Neurologic Deficits: Nondegenerative versus Degenerative Myelopathy

Abstract: Study Design  Retrospective review.Objective  Intraoperative motor evoked potential (MEP) monitoring in spine surgery may assist surgeons in taking corrective measures to prevent neurologic deficits. The efficacy of monitoring MEPs intraoperatively in patients with myelopathy from nondegenerative causes has not been quantified. We compared the sensitivity and specificity of intraoperative MEP monitoring in patients with myelopathy caused by nondegenerative processes to patients with degenerative cervicothoraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…9 The accuracy of MEPs in detecting potential neurological injury has been demonstrated by several studies. Clark et al 36 reported a sensitivity of 71% and a specificity of 94% in predicting postoperative deficits in patients undergoing operative procedures for degenerative cervical myelopathy. In 2004, Hilibrand et al 12 compared the use of both SSEP and tcMEP monitoring in 427 consecutive patients who underwent cervical spine surgery.…”
Section: The Use Of Ionm During Cervical Spine Surgerymentioning
confidence: 99%
“…9 The accuracy of MEPs in detecting potential neurological injury has been demonstrated by several studies. Clark et al 36 reported a sensitivity of 71% and a specificity of 94% in predicting postoperative deficits in patients undergoing operative procedures for degenerative cervical myelopathy. In 2004, Hilibrand et al 12 compared the use of both SSEP and tcMEP monitoring in 427 consecutive patients who underwent cervical spine surgery.…”
Section: The Use Of Ionm During Cervical Spine Surgerymentioning
confidence: 99%
“…[12][13][14][15] The most important aims of IONM are to prevent intraoperative nerve injury, facilitate more alert interventions, and safely complete surgery. The sensitivity of Tc(E)-MEPs is higher for DCM than for non-DCM 16 ; however, its effectiveness in cervical spondylotic myelopathy (CSM) and cervical OPLL has not yet been directly compared. OPLL is more susceptible to perioperative paralysis than CSM, [17][18][19] and the benefits of IONM for OPLL have already been demonstrated.…”
mentioning
confidence: 99%
“…The sensitivity of IONM was calculated to be 75% and specificity 98%, with differences depending on patient age and comorbidities as well as increased sensitivity in patients with preoperative motor deficits. A follow-up study by Clark et al 20 in 144 patients compared 102 patients with degenerative CSM and 42 patients with nondegenerative causes (24 extra-axial tumors, 12 infectious processes, 5 traumatic fractures, and 1 rheumatoid arthritis) who had IONM used during their surgery. For degenerative versus nondegenerative cases, a sensitivity/specificity of 71%/94% versus 33%/74% was identified respectively.…”
Section: Discussionmentioning
confidence: 99%